PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI CAÉ ACEH BERBASUS WEBSITE - Bustami; Muhammad Khairul Ammar; Mursyidin; Nazaruddin Ahmad (Prodi Teknologi Informasi UIN Ar-Raniry Bekerjasama dengan Pusat Penelitian dan Penerbitan LP2M Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This research is spurred by the absence of a dedicated website to showcase caé, coupled with the significant number of young Acehnese individuals in the information age who lack awareness about caé. Leveraging existing technology, the aim of this study is to develop a website-based centralized information system exclusively devoted to caé Aceh. This system not only offers public access to view the caé present in the database but also encourages users to suggest any caé that might not have been included yet. The primary objective of this system is to serve as a platform for preserving the nation's cultural heritage, with a specific emphasis on caé. Furthermore, it seeks to enhance the understanding of caé among the general public, particularly the younger generation in Aceh, and foster increased interest in studying Aceh caé through the website. The development process employed the prototype methodology, with experts conducting black box testing—a method where the system's internal workings are not disclosed—to ensure thorough evaluation. The testing results for this system yielded a perfect score of 100%, indicating its high suitability and effectiveness.